Tata Kelola Pembelajaran Berbasis Teknologi Informasi Dan Komunikasi Pada SMK Negeri 4 Makassar - Yahya, Dasriah M (Program Studi Administrsi Pendidikan Program Pascasarjana UNM, 2013)
This study aimed at discovering (1) the description on TIK-based management learning, (2) the role of teachers in TIK-based learninÂ and, (3) the supporting and inhibiting factors TIK-based learning at SMK Negeri 4 Makassar.The results of the study revealed that the management of TIK-based learning at SMKN 4 Makassar: the management of SMKN 4 Makassar had provided TIK facilities and the TIK facilities were not sufficient yet; whereas, the description on the management of learning process revealed that not all teachers conducted TIK-based learning. The roles of the teachers in TIK-based learning gave positive benefit for teachers and students in realizing learning objectives. The supporting factors on TIK-based lerning were TIK facilities were avalaible based on the needs and there was training for teachers on TIK; whereas, the inhibiting factors were TIK facilities were not sufficient yet, weakness on the organizing and monitoring, the electrical power was not sufficient, and low signal of internet network. KeyWords : ICT-based Learnin Management.